Mechanization outsourcing clusters and division of labor in Chinese agriculture - Zhang, Xiaobo; Yang, Jin; Reardon, Thomas (International Food Policy Research Institute, 2015)
Most of the poor in the developing countries are smallholder farmers. Improving their productivity is essential for reducing poverty. Despite small landholdings, a high degree of land fragmentation, and rising labor costs, agricultural production in China has steadily increased. If one treats the farm household as the unit of analysis, it would be difficult to explain the conundrum. When seeing agricultural production from the lens of division of labor, the puzzle can be easily solved. In response to rising labor costs, farmers outsource some power-intensive stages of production, such as harvesting, to specialized mechanization service providers, which are often clustered in a few counties and travel throughout the country to harvest crops at very competitive service charges. Through such an arrangement, smallholder farmers can stay viable in agricultural production.